2016
DOI: 10.1111/cga.12138
|View full text |Cite
|
Sign up to set email alerts
|

ToRCH “co‐infections” are associated with increased risk of abortion in pregnant women

Abstract: ToRCH infections (toxoplasmosis, rubella, cytomegalovirus and Herpes simplex virus) have long been known to be associated with bad obstetric outcomes. However, little information is available about the impact of ToRCH co-infections on the outcome of pregnancy. Hence, we tested the IgG and IgM antibodies to Toxoplasma gondii, Rubella, Cytomegalovirus and Herpes Simplex Virus among 81 pregnant women with abortion (case group) and 98 pregnant women with normal delivery (control group). In the single-infection mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…Marawan’s article pointed that TOX‐IgM‐positive tests were associated with seropositivity to HSV1‐IgG and HSV2‐IgM antibodies and that TOX‐seropositive patients were 1.94 and 1.35 times more likely than seronegative patients to have previous exposure to CMV and HSV‐1, respectively, which could be caused by that these infections are all linked to the poor socioeconomic conditions . In the study by Rasti et al, TOX‐IgG + CMV‐IgM and TOX‐IgG + HSV‐IgG + CMV‐IgM were the most frequent TORCH co‐infection patterns in the patients with abortion experience. Interestingly, the apparent TORCH co‐infection rates (201/19 000) by ELISA in Rasti’s report were pretty much comparable to that in our data, suggesting the similarity of the ELISA TORCH IgM screening power.…”
Section: Discussionmentioning
confidence: 99%
“…Marawan’s article pointed that TOX‐IgM‐positive tests were associated with seropositivity to HSV1‐IgG and HSV2‐IgM antibodies and that TOX‐seropositive patients were 1.94 and 1.35 times more likely than seronegative patients to have previous exposure to CMV and HSV‐1, respectively, which could be caused by that these infections are all linked to the poor socioeconomic conditions . In the study by Rasti et al, TOX‐IgG + CMV‐IgM and TOX‐IgG + HSV‐IgG + CMV‐IgM were the most frequent TORCH co‐infection patterns in the patients with abortion experience. Interestingly, the apparent TORCH co‐infection rates (201/19 000) by ELISA in Rasti’s report were pretty much comparable to that in our data, suggesting the similarity of the ELISA TORCH IgM screening power.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical CMV manifestations were assessed either with antenatal ultrasound or postnatal cCMV associated complications. The majority of the studies came from Israel (n = 19), where the primary clinical features included abnormal ultrasound, severe brain dysmorphology (mainly in the first and second trimesters), hearing abnormalities, as well as occult CNS symptoms that are associated with neurologic sequelae, abortion, premature deaths, and congenital malformations [71,74,[78][79][80][81][82][83][84][85][86]. On the other hand, some studies reported asymptomatic cCMV infections [87,88].…”
Section: Congenital CMV (Ccmv) In the Mena Regionmentioning
confidence: 99%
“…In the most severe cases of congenital infection, this virus might cause abortion and stillbirth. In milder cases, CMV congenital infection can cause hearing loss, vision loss, microcephaly, and seizure (3,4). The risk of primary CMV infection is around three percent, and 0.5% of live birth babies are born with congenital CMV infection (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In milder cases, CMV congenital infection can cause hearing loss, vision loss, microcephaly, and seizure (3,4). The risk of primary CMV infection is around three percent, and 0.5% of live birth babies are born with congenital CMV infection (3,4). Anti-CMV IgM antibody positivity indicates primary infections or reactivation of infection, both of which are associated with congenital abnormalities in pregnancy (5).…”
Section: Introductionmentioning
confidence: 99%